Accounting, auditing and governance for Takaful operations - Htay, Sheila Nu Nu; Rashid, Mohamed Arif; Soualhi, Younes; Zaharin, Hanna Rabittah; Shaugee, Ibrahim (John Willey & Sons, 2013)
Chapter 1 is presented as an introduction to takaful. Through the discussions in this chapter the reader should be able to grasp a basic understanding of the history and development of insurance (conventional) as well as takaful (Islamic insurance). This discussion also encompasses the differences between these two concepts. Furthermore, this chapter also explains the Shari’ah, legal and regulatory framework behind takaful operations as well as the basic takaful models being practiced around the world. Chapter 2 focuses on accounting and its relationship with takaful operators. This chapter starts out with a brief explanation of what is accounting and how it was developed. After that the discussion is aimed at providing a brief look at the operating environment of takaful operators – specifically the accounting and governance aspects. This includes the accounting and governance standards and guidelines as well as the organizations that set them. The discussion in this chapter is mostly focused on the standard setting organizations and institutions. Chapter 3 provides a detailed look at the financial reporting requirements of a takaful operator. Emphasis of this chapter is mostly on the requirements of the AAOIFI standards for takaful operators. Furthermore this chapter also provides typical journal entries that a takaful operator has to pass in order to record its transactions including Retakaful. Chapter 4 discusses financial statement analysis. The discussion is from the perspective of a takaful operator hence is different from a typical financial statement analysis. The ratios discussed in this chapter include underwriting, profitability as well as liquidity ratios. The ratios are grouped according to the source of funds – General takaful fund, family takaful fund and shareholder’s fund. Readers should be able to calculate the ratios as well as describe the results and make sense of the financial statements of a takaful operator after reading this chapter. Chapter 5 focuses on zakat – computation and distribution – for takaful operators. The discussion is started with an introduction to zakat and its relation to the Islamic worldview. After that, the discussion is moved on to zakat computation for takaful operators. The discussion here is based on the methods suggested by AAOIFI. After discussing computation the chapter is ended with a look at the disclosure requirements as suggested by AAOIFI. Chapter 6 provides a detailed look at the auditing and governance standards that a takaful operator has to follow. The standards discussed include those set by AAOIFI, IFSB, BNM and Bursa Malaysia.